2018
DOI: 10.1007/s00226-018-1027-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential field-deployable NIRS identification of seven Dalbergia species listed by CITES

Abstract: Near-infrared spectroscopy (NIRS) is a potential, field-portable wood identification tool. NIRS has been studied as tool to identify some woods but has not been tested for Dalbergia. This study explored the efficacy of hand-held NIRS technology to discriminate, using multivariate analysis, the spectra of some high-value Dalbergia wood species: D. decipularis, D. sissoo, D. stevensonii, D. latifolia, D. retusa, all of which are listed in CITES Appendix II, and D. nigra, which is listed in CITES Appendix I. Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…In this case, it should be the cell walls. At the same time, grenadilla has been known to possess high level of extractives, which is a non-structural part of the wood but still contribute to its mass (Donnelly et al 1975;Sjostrom 1993). Yin et al (2018), specifically, have conducted a thorough study regarding the extractives of grenadilla wood and found that the extractive percentage could reach up to 16.05% from extractions using a mixture of benzene/ethanol alone.…”
Section: Comparison With Past Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it should be the cell walls. At the same time, grenadilla has been known to possess high level of extractives, which is a non-structural part of the wood but still contribute to its mass (Donnelly et al 1975;Sjostrom 1993). Yin et al (2018), specifically, have conducted a thorough study regarding the extractives of grenadilla wood and found that the extractive percentage could reach up to 16.05% from extractions using a mixture of benzene/ethanol alone.…”
Section: Comparison With Past Studiesmentioning
confidence: 99%
“…In 2017, CITES added grenadilla wood, together with all other wood species from the Dalbergia genus, to its appendix of endangered species (Snel et al 2018). Such a decision was justified by the ever-increasing pressure of the demand of this wood, insufficiently compensated by plantation efforts: Grenadilla is a slowgrowing tree species, with time needed to reach mature size ranging from 50-80 to 70-100 years (Malimbwi et al 2000;Ball 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional methods of wood identification include manual comparison, dichotomous keys, multiple entry keys, punch card search and computer database program search [ 1 ]. Researchers have also tried to use DNA molecular marker technology [ 2 ], near-infrared spectroscopy technology [ 3 ], GC-MS technology [ 4 ], computer vision technology [ 5 ] and other auxiliary identification methods to improve the accuracy of traditional methods in wood identification and speed the process of identifying wood species.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional methods of wood identification include manual comparison, dichotomous keys, multiple entry keys, punch card search and computer database program search (Wheeler & Baas 1998). Researchers have also tried to use DNA molecular marker technology (Yu et al 2017), near-infrared spectroscopy technology (Snel et al 2018), GC-MS technology (Wang et al 2018), computer vision technology (Hwang et al 2018) and other auxiliary identification methods to improve the accuracy of traditional methods in wood identification and speed the process of identifying wood species.…”
Section: Introductionmentioning
confidence: 99%